AN EXAMINATION OF ONE FACTOR IN SCHOOL REFORM: INCREASED TEACHER ACCOUNTABILITY IN TWO URBAN SCHOOL DISTRICTS - Nadine Bonda (Universidade Federal de Sergipe, 2018)
Beginning in 2009, and with the passage of the American Recovery and Reinvestment Act of 2009, school districts across the United States began to be held to higher standards and their progress publicly reported.  Student achievement began to be measured by standardized testing and great efforts were being made to reduce the achievement gap. This paper is based on a five-year study of teacher evaluation in two urban districts in Massachusetts where improving teacher practice was seen as an important factor in raising student achievement. This research studied efforts to address those teachers who were identified as underperforming and were supported through individual improvement plans.  This paper used a case study approach to show what the practices of a sampling of these teachers looked like, teachers' reactions to being rated unsatisfactory, and teachers' reactions to the improvement planning process.